The difficulties of, and the threats to, the Polish family in the 1960s in questionnaires published in „The Life of Warsaw” - Krakowiak, Małgorzata (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The article presents the picture of a family, based on the analysis of questionnaires devised by the Author. The surveys were sent between 1962–1969 to the editorial office of the „Life of Warsaw”. They appeared periodically. The first of them was entitled „What is you family like?”. The main purpose was to get the knowledge about transformations of contemporary families and social-economic changes which shaped the model of a family. The next two surveys „Young couples” and „Husband and Wife” aimed to discover relationships and marital problems which were appearing in the 1960s. Another questionnaire „Parents, children, parents” was expected to make the diagnosis of ideological conflicts, behavioral problems, as well as relations between parents and children and related problems. The last survey „When they both work” showed a picture of the ordinary family life in which the husband and wife worked professionally. It should be emphasized that the questionnaire did not have the form of detailed surveys. They had an opened-question form which resulted in the collection of multipage descriptions of personal histories.
Keywords: family; „The Life of Warsaw”; family problems; The Polish People’s Republic